Relationship between dementia severity and behavioural and psychological symptoms in early‐onset Alzheimer's disease. Issue 4 (3rd March 2015) - Tanaka, Hibiki; Hashimoto, Mamoru; Fukuhara, Ryuji; Ishikawa, Tomohisa; Yatabe, Yusuke; Kaneda, Keiichiro; Yuuki, Seiji; Honda, Kazuki; Matsuzaki, Shiho; Tsuyuguchi, Atsuko; Hatada, Yutaka; Ikeda, Manabu
Abstract: Background: The features of behavioural and psychological symptoms of dementia (BPSD) are influenced by dementia stage. In early‐onset Alzheimer's disease (EOAD), the association between BPSD and dementia stage remains unclear because of the difficulty of recruiting subjects with a wide range of disease severity. We used a combination of community‐based and hospital‐based approaches to investigate the relationship between dementia severity and BPSD in EOAD patients. Methods: Sixty‐three consecutive EOAD outpatients and 29 EOAD patients from a community‐based survey were divided into three dementia severity groups according to the Clinical Dementia Rating scale (CDR): mild (CDR 0.5–1, n = 55), moderate (CDR 2, n = 17), and severe (CDR 3, n = 20). BPSD were rated using the Neuropsychiatric Inventory. Results: Scores of the Neuropsychiatric Inventory subscales agitation, euphoria, apathy, disinhibition, irritability, and aberrant motor behaviour increased significantly with increased dementia severity. Hallucinations were greater in the moderate group than in the mild group. For delusions, depression, and anxiety, no significant differences were observed among the three severity groups. Conclusions: The pattern of apathy, agitation, disinhibition, irritability, and aberrant motor behaviour worsening with severity progression in EOAD is similar to the pattern in late‐onset Alzheimer's disease. In contrast, hallucinations, depression, and anxiety showed different patterns in EOAD.